Effect of metakaolin utilization ratio and loop method-pre-shearing process variation on rheological properties of cementitious systems having different C3A content. (February 2023) - Biricik, Öznur; Şahin, Hatice Gizem; Mardani, Ali
Abstract: Thixotropic behavior, which directly affects the fresh state properties of cementitious systems such as pumpability, compressibility and hydrostatic mold pressure, is determined by applying the loop method, step change and constant shear rate. This behavior is seriously affected by parameters such as the type, amount and fineness of the binder and the process applied in rheological measurements. In this study, the effect of cement C3 A content, metakaolin utilization ratio, resting time of the mixture, pre-shear rate and applying pre-shear rate on the thixotropic behavior of the mixtures at the beginning and 20th-minutes were investigated. For this purpose, 4 types of cement having different C3 A contents (2.13%, 3.60%, 6.82% and 9.05%) were used. By testing each of the 4 cements (2.13%, 3.60%, 6.82% and 9.05%) for 5 conditions (no metakaolin, 3%, 6%, 9% and 12% metakaolin), a total of 20 mixtures were prepared. For each cement type, 0, 3, 6, 9 and 12% of the total binder volume was replaced with metakaolin. The loop method was used to determine the rheological parameters. According to the results, irrespective of all parameters examined, the structural build-up area values were higher than the structural breakdown ones in the mixtures and the structure formation that occurred after 20 min was mostly reversible. It was determined that rheological parameters, structural build-up area value and rate of reversible structure formation increased with the increase in cement C3 A content and metakaolin utilization rate. The increase in the initial dynamic yield stress values of the mixtures with the increase of the cement C3 A ratio was more pronounced in the case where the measurement is made without waiting immediately after the pre-shear application. The effect of C3 A content on dynamic yield stress and viscosity values was more pronounced with an increasing pre-shear rate. The opposite was observed for the structural build-up area values. Highlights: Structural build-up area values were higher than structural break-down area values. It was determined that rheological parameters increased over time. Structure formation that occurs after 20 min in mixtures is mostly reversible. The highest area value was measured in the mixture with the highest C3 A ratio. It was determined that rheological parameters increased with addition of metakaolin.